Improving Narrative Writing Skills Using Picture and Picture Models Assisted by Zoom Media in Class III SD Incasi Raya Gunas 01 Pesisir Selatan - Jendriadi; Desmariani, Evi; Efendi, Amrizal (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research is motivated by the results of a preliminary study conducted in class III of the Incasi Raya Gunas 01 Pesisir Selatan Elementary School, that the process of writing narratives in Indonesian language learning has not been carried out optimally. This study aims to describe the improvement of narrative writing skills with picture and picture models in third grade elementary school students Incasi Raya Gunas 01 Pesisir Selatan. This study uses a qualitative and quantitative approach, with the type of Classroom Action Research. This research was conducted in two cycles, with the stages of planning, implementing, observing and reflecting. This research was conducted in the second semester of the 2020/2021 academic year at SD Incasi Raya Gunas 01 Pesisir Selatan. The research subjects were teachers and third grade students of SD Incasi Raya Gunas 01 Pesisir Selatan. Data collection techniques used are observation, test, documentation. While the research instruments are observation sheets, test sheets, photos. This study shows that the learning process of composing narratives using the Picture and Picture model can improve the learning process of students in learning Indonesian in class III SD Incasi Raya Gunas 01 Pesisir Selatan. This can be seen from: 1) The improvement of narrative essay writing skills with the Picture and Picture model at the pre-writing stage in the first cycle, the average percentage obtained is 75.9% with Good increasing in the second cycle 89.2% (an increase in 13,4%), very good criteria 2) The improvement in the writing stage was carried out by the researcher conveying the learning steps using the Picture and Picture model , in the first cycle, the average percentage obtained was 51.9 % with sufficient criteria (C) increased in the second cycle 91.7% (an increase of 35.4%) with very good criteria 3) The improvement in the post-writing stage in the first cycle, the average percentage obtained was 59.1% with the Enough (C) criteria, the increase in the second cycle was 91.7% (32.6% increase) with the Very Good criteria.